-1,9y-(y-0,6)+0,3*(4y-0,3)=0

Simple and best practice solution for -1,9y-(y-0,6)+0,3*(4y-0,3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1,9y-(y-0,6)+0,3*(4y-0,3)=0 equation:



-1.9y-(y-0.6)+0.3*(4y-0.3)=0
We multiply parentheses
-1.9y-(y-0.6)+1.2y-0.09=0
We get rid of parentheses
-1.9y-y+1.2y+0.6-0.09=0
We add all the numbers together, and all the variables
-1.7y+0.51=0
We move all terms containing y to the left, all other terms to the right
-1.7y=-0.51
y=-0.51/-1.7
y=0.51/1.7

See similar equations:

| 2+.25x=-8+1.5x | | 1q+2=6q-(-2)+8q+4 | | 6=v/4=8 | | 5c+9=-41 | | 5.4x+9=63 | | 16m^2-24m= | | 12d-20=10d-12 | | 2x+x+(x-5)=130 | | 3x=12x$15.73 | | 9^2-9y+18=0 | | 4r+4=2r-3/4 | | 11x-13=9x-3 | | 3t-5=6t-4 | | x^2(x+1)=440 | | 5x+2+6x−12=180 | | 1,4x-12=0.9x+4 | | y=-62,501.68+38,258.82+-2,928.10^2 | | -3x=36+3 | | 2/3=x+4/8 | | 5r-4=4r+6 | | 6^6x-6=33 | | 10p+15(1-p)= | | B=2000−100t | | –x+8x−–3x+–13x=–12 | | (3x+2)-(8x+6)=14 | | 3x+26+x+20=180 | | 85=1.8x-76.9 | | 5x+4=x+16=3(4x-2) | | 6^2x.9^x=18 | | 9-6x-2+4x=3 | | 5(2y+7)=40 | | 127+10x+7+5x+3=360 |

Equations solver categories